Les Marededéus sagraris de Mallorca - Llompart Moragues, Gabriel (Miscel·lània litúrgica catalana, 2006)
Majorca?s insularity has determined some aspects of its artistic heritatge. A series of large Madonnas used as ciboria or receptacles of the eucharistic reservation has been discovered in the diocese. It starts with an image that overlooked the Ghotic altarpiece of the cathedral (15th century) and seems to have gained momentum at the turn from the 15th to the 16th century. Its most important author is the sculptor priest Gabriel Moger. This peculiar, theologically based archaism seems to have been inspired by Durandus de Mende.